Petrography, Geology Structure and Landslide Characterization of Sumatra Fault Deformation: Study Case In Km 10-15 Highway, Koto Baru Sub District, West of Sumatra - Cahyaningsih, Catur; Crensonni, Puja Fransismik; Aditia, Yogi; Suryadi, Adi; Yuskar, Yuniarti; Choanji, Tiggi; Putra, Dewandra Bagus Eka (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
Research area is around Tanjung Balik, Koto Baru Sub Base, Lima Puluh Kota District, West Sumatra Province. Located along the highway Km 10-15 Riau – West Sumatra and the coordinate around 00˚08'40 '' LU - 0˚11'20 '' N and 100˚45'20 '' BT - 100˚47'00 '' BT. The purpose of research to identify petrography, microstructure, types of landslides and the geological condition. The methods using polarization microscope, stereography, landslide identification survey and geological mapping. The result of study shows the petrography analysis of lithology of study area are classified into three types of rocks are Feldspathic Greywacke, Lithic Arenite, and Slate. Microstructures trending system show the foliation structure that is relatively Southeast-Northwest. Types of landslide which dominates in the research area are debris avalanche and translational landslide. Geological analysis show some of rock units are classified into two units: Sandstone Unit and Slate Unit. Sandstone Unit spread in the northern part of the study area, while Slate Unit spread in the southern part of the study area. The characteristics of these rocks showed Pematang Formation.